2012
DOI: 10.1177/0021998312454907
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of one-dimensional thermal response of silica-phenolic composites with volume ablation

Abstract: The silica-phenolic composites experience volume ablation when exposed to a radiant heat flux. Based on the analysis of mechanisms during volume ablation, a mathematical model was developed to predict the one-dimensional thermal response of the ablative material in this paper. After discretizing the space and time domain, the governing equations were described using the implicit finite differential form. Both the heat-mass transfer process and the moving boundary caused by thermal expansion, as well as the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The thermal analysis which involves a mathematical model to predict the one‐dimensional (1D) thermal response of ablative materials was conducted to determine the temperature profile through the composite when exposed to one‐sided radiant heating. The detail description of the model has been reported in our previous article . In the model, the coupling heat‐transfer process, generation of pyrolysis gases and their subsequent diffusion process were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal analysis which involves a mathematical model to predict the one‐dimensional (1D) thermal response of ablative materials was conducted to determine the temperature profile through the composite when exposed to one‐sided radiant heating. The detail description of the model has been reported in our previous article . In the model, the coupling heat‐transfer process, generation of pyrolysis gases and their subsequent diffusion process were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 shows the decomposition degree contours of the glass fiber phenolic resin composite, which equals one minus F, which is defined in Equation (4). In fact, decomposition degree is the expression of dimensionless treatment of density, which is usually used for relative research [29,47,48]. Namely, the decomposition degree of 0 represents the fact that the material density is the virgin density, and the decomposition degree of 1 represents that the material density is the char density.…”
Section: Field Of Temperaturementioning
confidence: 99%
“…This numerical model, which was mainly based on the model by Chippendale et al [24], considered the processes of the thermal transport, the polymer degradation, the pyrolysis gases transport, and the carbon fiber sublimation in the composite. The model formulations [24][25][26][27][28][29][30][31][32][33][34][35][36] and the calculation parameters [18,24,29] Figure 8 shows the temperature field and the internal gas pressure distribution in the composite along the thickness direction with a laser irradiation time of 1 ms (1 pulse duration). From the temperature profiles of Figure 8, it could be found that a higher laser peak power density led to a faster temperature rise and a faster heat transfer in the composite.…”
Section: Simulation Of the Internal Gas Pressurementioning
confidence: 99%
“…Because the pyrolysis gases did not absorb and shield the laser energy, the laser energy received by the composite surface was equal to the output energy of the laser. Although the pyrolysis gases that were released from the composite surface changed the ambient temperature and the convective heat transfer on the surface [29,[34][35][36], the effect of the pyrolysis gases on the surface heat exchange was much less than the effect of the absorbed laser fluence in the model was. Therefore, the boundary conditions of the laser drilling process could be represented as follows:…”
Section: Conflicts Of Interestmentioning
confidence: 99%